A Case of Adult-Onset Still’s Disease Caused by a Novel Splicing Mutation in TNFAIP3 Successfully Treated With Tocilizumab - Lawless, Dylan; Pathak, Shelly; Scambler, Thomas Edward; Ouboussad, Lylia; Anwar, Rashida; Savic, Sinisa (Frontiers in Immunology, 2018)
TNFAIP3 encodes the NF-κB regulatory protein A20. High-penetrance heterozygous mutations in TNFAIP3 cause a haploinsufficiency of A20 (HA20), inadequate inhibition of NF-κB pathway and an early onset autoinflammatory disorder. However, the clinical phenotype of patients with HA20 varies greatly and clinical diagnoses prior to establishing the genetic cause, included both autoimmune and autoinflammatory conditions. Here we present the first patient with HA20, who was previously diagnosed with AOSD but was later found to have a novel heterozygous variant in TNFAIP3 and who was successfully treated with anti-IL6 receptor biologic tocilizumab (RoActemra). We discovered a novel heterozygous mutation in TNFAIP3 c.1906C>T, not previously found in ExAC database. Further analysis shows that this single nucleotide variant at the terminal residue of TNFAIP3 exon 7 produces an alternatively spliced mRNA resulting in p.His636fsTer1. Additional genetic analysis of family members shows that this variant does segregate with the inflammatory clinical phenotypes. Subsequent functional test show that NF-κB activation, measured as intracellular phosphorylation of p65 in CD14+ monocytes, was more enhanced in the patient compared to healthy controls (HC) following stimulation with LPS. This was associated with higher production of inflammatory cytokines by the patients PBMC in response to LPS and ATP and enhanced activation of NLRP3 inflammasome complex. Furthermore, increased activation of NLRP3 inflammasome was evident systemically, since we detected higher levels of ASC specks in patients’ sera compared to HC. Finally, we used population genetics data from GnomAD to construct a map of both genetic conservation and most probable disease-causing variants in TNFAIP3 which might be found in future cases of HA20.